Associations between air pollutants and blood pressure in an ethnically diverse cohort of adolescents in London, England. - A Karamanos; Y Lu; I S Mudway; S Ayis; F J Kelly; S D Beevers; D Dajnak; D Fecht; C Elia; S Tandon; A J Webb; A J Grande; et al. (PLoS ONE)
Longitudinal evidence on the association between air pollution and blood pressure (BP) in adolescence is scarce. We explored this association in an ethnically diverse cohort of schoolchildren. Sex-stratified, linear random-effects modelling was used to examine how modelled residential exposure to annual average nitrogen dioxide (NO2), particulate matter (PM2.5, PM10) and ozone (O3), measures in μg/m3, associated with blood pressure. Estimates were based on 3,284 adolescents; 80% from ethnic minority groups, recruited from 51 schools, and followed up from 11-13 to 14-16 years old. Ethnic minorities were exposed to higher modelled annual average concentrations of pollution at residential postcode level than their White UK peers. A two-pollutant model (NO2 & PM2.5), adjusted for ethnicity, age, anthropometry, and pubertal status, highlighted associations with systolic, but not diastolic BP. A μg/m3 increase in NO2 was associated with a 0.30 mmHg (95% CI 0.18 to 0.40) decrease in systolic BP for girls and 0.19 mmHg (95% CI 0.07 to 0.31) decrease in systolic BP for boys. In contrast, a 1 μg/m3 increase in PM2.5 was associated with 1.34 mmHg (95% CI 0.85 to 1.82) increase in systolic BP for girls and 0.57 mmHg (95% CI 0.04 to 1.03) increase in systolic BP for boys. Associations did not vary by ethnicity, body size or socio-economic advantage. Associations were robust to adjustments for noise levels and lung function at 11-13 years. In summary, higher ambient levels of NO2 were associated with lower and PM2.5 with higher systolic BP across adolescence, with stronger associations for girls.